Assessment of quantity and quality indicators of water resources in the Zarafshan river basin (within the territory of Uzbekistan) - Gapporov Khairullo; Kulmatov Rashid; Opp Christian (E3S Web of Conferences)
In the context of climate change and growing antrophogenic activities, the depletion and pollution of water resources is a global concern, posing significant threats worldwide. This study evaluates the volume and quality of water resources, the heavy metal concentrations, the total mineralization and the quantity of collector-drainage waters, and the primary factors contributing to the pollution of the Zarafshan River in Uzbekistan, based on in situ data from 2013 to 2023. The perennial results show that the average annual indicator of the volume of collector-drainage water has increased from 2,787 million m3 to 3,418 million m3, the amount of salts grow up 2,914 thousand tons from the annual average of 4,808,000 tons. The heavy metal concentrations (Cu, Zn, Cr (VI)) were analyzed from the upper part to the lower part of the Zarafshan River. Cu has increased from 1.3 times to 1.35 times, Zn has increased from 1.2 times to 4.7 times, Cr (VI) hasincreased from 1.1 times to 8 times over the years from 2013 to 2023. Long-term research show the mineralization of the water of the Zarafshan River has increased from the upper part of to the lower part within the territory of Uzbekistan from 3.9 to 6.5 times in the observed years. The minimum average annual salinity value of collector-drainage water in the Zarafshan River basin is 0.79 g/L in the Samarkand region, while the highest value is 2.9 g/L in the Navoi region.